2006
DOI: 10.1038/emm.2006.85
|View full text |Cite
|
Sign up to set email alerts
|

No association of prion protein gene polymorphisms with Alzheimer's disease in Korean population

Abstract: The polymorphism at codon 129 (M129V) of the human prion protein gene (PRNP) is a known risk factor for Creutzfeldt-Jakob disease (CJD) in Caucasians. There are few reports of this polymorphism's effect on memory and on the risk of Alzheimer's disease (AD). The M129V genotype distributions among Asians are very different from Caucasians. Another polymorphism, codon 219 (E219K) is not found in Caucasians. We investigated two polymorphisms of PRNP, M129V (rs1799990) and E219K (rs1800014) in 297 Korean AD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
9
1
1
Order By: Relevance
“…Similarly, findings on the influence of PRNP*129Val in the risk of AD, another neurodegenerative disorder, have been well defined despite ethnic background discrepancies. Previous studies have reported that this variant is significantly associated with AD in Dutch [13], German [14], and Polish populations [15], in contrast to the findings from studies involving Korean [16], Spanish [17], and Italian [18] populations. Furthermore, it has been known that homozygosity for codon 129 (M or V allele) is connected with early-onset AD [13,17].…”
Section: Introductioncontrasting
confidence: 48%
“…Similarly, findings on the influence of PRNP*129Val in the risk of AD, another neurodegenerative disorder, have been well defined despite ethnic background discrepancies. Previous studies have reported that this variant is significantly associated with AD in Dutch [13], German [14], and Polish populations [15], in contrast to the findings from studies involving Korean [16], Spanish [17], and Italian [18] populations. Furthermore, it has been known that homozygosity for codon 129 (M or V allele) is connected with early-onset AD [13,17].…”
Section: Introductioncontrasting
confidence: 48%
“…A similar conclusion was reached in a Japanese study based on a large sample of AD patients where the genotypic analysis of codon 129 of the PRNP gene showed no association with either early-onset (EO) or late-onset (LO) form of the disease [13]. In two AD Korean samples the distribution of the polymorphic codon 129 as well as the 219 of the PRNP gene was no different from normal controls underlying contrasting evidences on this issue and confirming the important role related to ethnicity [14,15].…”
Section: Introductionmentioning
confidence: 87%
“…Two hundred and forty-eight Korean AD patients and 224 cognitively healthy control subjects were recruited from the Samsung Medical Center in Seoul and the Ansan cohort, respectively, as described previously [19] . The cognitive functions and memory impairment of controls were assessed using the Consortium to Establish a Registry for Alzheimer's Disease neuropsychological battery [20] .…”
Section: Subjects and Blood Samplingmentioning
confidence: 99%